Oral care agent
By using core-shell structure composite materials composed of porous silica particles and β-cyclodextrin, the povidone iodine is effectively protected and dispersed, and its stability and dispersion problems in oral care products are solved, achieving efficient and stable bactericidal effect and sustained release effect.
Patent Information
- Application Number
- CN202411494191.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-11
AI Technical Summary
The existing povidone iodine has problems such as low stability, poor dispersion, susceptibility to light decomposition, and difficult to maintain effective iodine content in oral care products, which affects its application in oral care.
A composite material with a core-shell structure is used, with porous silica particles as the core, povidone iodine is distributed in its internal pores, and β-cyclodextrin is used as the shell, covering the silica particles to form a "external hydrophilic and internal hydrophobic" structure, protecting the povidone iodine from light, oxygen, heat, and water.
It improves the stability of povidone iodine, maintains its high effective iodine content, and has a sustained release effect, extends the effective use time of antibacterial agents. At the same time, the composite material has good dispersion performance and stability in oral care products.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oral care, and in particular relates to a composite material used for an oral care agent. The composite material can be directly used in oral care agent products such as toothpaste as an abrasive and an antibacterial agent. Background Art
[0002] With the continuous development of social economy, people are paying more and more attention to the impact of teeth and oral hygiene on health. Dental caries and periodontal disease are considered to be the most common oral diseases in the world, which not only affect the quality of life of patients, but also cause economic losses to patients. The microbiome in the oral cavity of a healthy human is in a balanced state. If the diet and oral hygiene are not in place, or if irritating oral products are used, pathogenic bacteria will be more likely to gather on the teeth and reproduce, destroying the balance of the oral microecology and forming pathogenic dental plaque biofilm. Dental plaque is the main cause of many oral diseases such as dental caries and periodontal disease. Therefore, how to inhibit and remove dental plaque has attracted great attention.
[0003] Oral hygiene is an important means of preventing and treating oral diseases. The most common traditional daily oral hygiene method is brushing teeth with toothpaste containing antibacterial agents. This type of toothpaste usually contains antibacterial substances for improving oral health in the toothpaste body mainly composed of abrasives, moisturizers, thickeners, foaming agents, fragrances, and water. Antibacterial substances are mainly divided into inorganic antibacterial agents, organic antibacterial agents, and biological antibacterial agents. Among them, inorganic antibacterial agents such as metal element antibacterial agents are mainly metals and their compounds, such as Ag, Zn, titanium oxide, etc. The bactericidal mechanism of metal elements has a saying that metal ions can affect the ion concentration difference inside and outside the microbial membrane, thereby hindering or destroying the physiological needs of cells; another saying is that metals are complexed with nitrogen and oxygen elements in enzyme proteins, destroying metal ions that maintain the activity of enzyme proteins, and the cells catalyzed by them lose their functions. TiO2 has high oxidation activity. After absorbing near-ultraviolet light waves, its valence band electrons will be excited to highly active negative electrons, and positively charged holes will be formed along with the loss of electrons in the valence band, which can convert its surface OH -Oxidized with H2O to ·OH free radicals, ·OH free radicals have strong oxidizing properties, can destroy the structure of bacteria and other microorganisms, and can quickly and permanently kill bacteria and other microorganisms. For example, CN103385804A discloses a nano-silver mouthwash for preventing and treating oral diseases, including 0.1ppm to 1000ppm nano-silver. The principle is that silver particles with a diameter of 10 to 50 nanometers can be adsorbed on the cell membrane of harmful microorganisms, and by interfering with their metabolism, damage protein capsids and DNA molecules to cause their death. It has a broad-spectrum bactericidal and antibacterial effect, has a long-lasting and effective effect, has no toxic side effects, does not produce drug resistance, is safe and reliable, and is easy to use. Biological antibacterial agents mainly include simple extracts of natural animals and plants, microorganisms and natural materials, such as amino acids, natural peptides and high-molecular sugars, such as coptis chinensis, houttuynia cordata, propolis, wild chrysanthemum extracts, etc. CN115487105A discloses a Chinese herbal toothpaste for fresh breath, which comprises, by weight: 34-75 parts of Chinese herbal extracts, 2-7 parts of abrasives, 5-10 parts of moisturizers, 3-10 parts of surfactants, 0.5-1 parts of thickeners, 0.5-1 parts of preservatives, and 0.3-1 parts of pH regulators. The Chinese herbal toothpaste can help smokers to have long-lasting fresh breath, and it has excellent stability and strong cleaning power; US20130224125A1 discloses an antibacterial mouthwash composition based on microemulsion, which comprises a unique water-soluble matrix complex, at least one antimicrobial agent that is immiscible or insoluble in water, and optional preservatives or preservative systems, weak carboxylic acids, colorants and other additives, and examples of antimicrobial agents include menthol, thymol, eucalyptol and / or methyl salicylate, which have improved antibacterial efficacy. There are many types of organic antibacterial agents, mainly including: organic halides, such as sodium pentachlorophenol; alcohols, such as ethanol phenols, such as p-nitrophenol; aldehydes, such as glutaraldehyde; ketones, such as o-hydroxycyclopentenedione; esters, such as dimethyl fumarate; nitriles, such as chlorhexidine; and pyridines, imidazoles and thiazolines. Organic antibacterial agents have both bactericides and preservatives. They are the most widely used raw materials in antibacterial agents. However, considering the safety of oral care agents to human bodies, the most commonly used organic antibacterial agents are chemical antibacterial agents such as triclosan, chlorhexidine, and PVP-iodine (polyvidone-iodine). However, chemical antibacterial agents are still limited to the mechanism of sustained-release antibacterial, with a short action time. Short-term oral use can eliminate oral bacteria, but long-term use can cause tooth discoloration and oral dryness. At the same time, chemical antibacterial agents are susceptible to the influence of other substances in the formula, producing antagonistic effects. CN113244262A discloses a powder mist inhalation preparation for the prevention and treatment of respiratory infectious diseases, the powder mist inhalation preparation comprising iodine molecules and / or pharmaceutically acceptable carriers as active substances. Inhaled into the respiratory tract or lungs by powder mist, it is used for the prevention and treatment of respiratory and pulmonary infectious diseases, with the advantages of direct targeting at the infection site, rapid onset, small dosage, and small side effects.CN106163577A discloses a stable composition of uncomplexed iodine comprising molecular iodine (I2) and an acceptable iodate (IO3. - ) source and acid (inorganic acid or organic acid), the concentration of uncomplexed molecular iodine is an effective amount for disinfection, biocidal and / or antimicrobial (depending on the final use of the composition), and can be used as a disinfectant solution, bactericide and / or microbicide (for example, antiviral, antibacterial, antifungal, antispore, etc.) for various surfaces and solutions (including living and non-biological surfaces). It can be seen that iodine has the advantages of high efficiency and low toxicity, long action time, and bacteria having no drug resistance to it as a bactericidal material, so its application in sterilization is highly valued. However, due to the low water solubility and toxicity of iodine, its application in oral care products sterilization is limited, and iodine is listed as a prohibited ingredient in the national standards for toothpaste and mouthwash. In order to expand the application scope of iodine, iodine is loaded on polyvinylpyrrolidone to form an amorphous complex, namely povidone-iodine, which gradually releases iodine when needed. It is an efficient and broad-spectrum disinfectant, which overcomes the shortcomings of low iodine solubility, instability, and easy allergic reactions. It has the advantages of low irritation and light pollution. It is approved by the Chinese Pharmacopoeia as a disinfectant that can be directly used by the human body. For example, CN110037940A discloses an oral sterilization and disinfection mouthwash, and specifically discloses the weight percentage of each component as follows: povidone-iodine 4.5% to 5.5%; potassium iodate 0 to 0.05%; potassium iodide 0.1% to 0.15%; polyvinylpyrrolidone 0.5% to 0.8%; sodium lauryl sulfate 0.05% to 0.1%; glycerol 1% to 3%; polyethylene glycol 400
[0004] 0.4% to 0.6%; citric acid 0.15% to 0.25%; auxiliary materials 0% to 0.1%; freshener 0.5% to 1.2%; purified water as the balance. The mouthwash has the characteristics of good sterilization and disinfection effect, low irritation, harmlessness to the human body, good stability and long storage time. CN1245954C discloses a povidone-iodine toothpaste, which comprises the following ingredients by weight: 1% povidone-iodine, 0.01-0.03% potassium iodate, 0.5-1.5% sodium carboxymethyl cellulose, 2-3% sodium lauryl sulfate, 0.5-1% sodium alginate, 13-18% sorbitol, 25-30% glycerol, 15-20% silicon dioxide, 0.05-0.15% sodium saccharin, 0.5-1% peppermint oil and 29-34% purified water. When used, a large amount of foam can be generated, which is in full contact with the tooth part, thus increasing the retention time and having a good effect on inhibiting the formation of dental plaque. At the same time, brushing teeth with the povidone-iodine toothpaste has the effect of mechanically removing dental plaque, and the combination of the two can effectively inhibit the formation of dental plaque.
[0005] Although povidone iodine has good water solubility, the polyvinyl pyrrolidone in its structure is a high molecular polymer, which is easy to agglomerate in the process of being dissolved in water, and has poor dispersibility, resulting in a long dissolution process and uneven dispersion in the preparation process of oral care agents. In addition, povidone iodine is easily decomposed and sublimated by light during storage, and the content of effective iodine is reduced and cannot reach the effective bactericidal concentration, which brings inconvenience to production, storage, and use. It can be seen that it is of great significance to develop a low-cost, environmentally friendly, easy to store and use povidone iodine oral care agent composite material with high stability. Summary of the invention
[0006] In order to solve the defects in the prior art, the present application provides an oral care agent, in particular, a composite material for oral care agents, the composite material is a core-shell structure, the core is a porous silica particle, povidone iodine is distributed in the pores of the porous silica particles, and the shell is β-cyclodextrin. The composite material of this specific structure can effectively disperse the antibacterial agent povidone iodine into the internal pores of the porous silica particles, and the β-cyclodextrin with a "hydrophilic outside and hydrophobic inside" structure can effectively coat it, and the silica is coated in the internal cavity of the β-cyclodextrin, further isolating the contact between povidone iodine and free water, so that povidone iodine is protected from the influence of light, oxygen, heat, and water, thereby improving the stability of the antibacterial substance povidone iodine and maintaining its higher effective iodine content. In addition, β-cyclodextrin can be degraded by digestive enzymes and microorganisms in the human body, and as a common carbohydrate, it participates in the body's metabolism without accumulation, and is an ideal inclusion carrier, and is safe and non-toxic to use. In addition, β-cyclodextrin also has certain antibacterial properties. When the composite material is used in oral care agents, such as toothpaste or mouthwash, the β-cyclodextrin will gradually destroy the integrity of the coating layer under the action of friction or digestive enzymes in saliva, so that the internal povidone iodine active ingredient comes into contact with water and gradually releases effective iodine for sterilization and disinfection. It can be seen that in addition to high stability, the composite material also has a certain sustained-release effect, which increases the effective use time of the antibacterial agent.
[0007] In order to achieve the above-mentioned purpose of the invention, the present application provides a composite material for oral care agent, wherein the composite material is a core-shell structure, wherein the core is porous silica particles, povidone iodine is distributed in the pores of the porous silica particles, and the shell is β-cyclodextrin.
[0008] As a further improvement of the present invention, the diameter of the porous silica particles is 50 to 300 nm, preferably, the diameter of the porous silica particles can be 100 to 300 nm, 150 to 250 nm, 180 to 200 nm, etc., but not limited thereto. The average pore size of the porous silica particles can be 1 to 70 nm, preferably, 5 to 60 nm, 7 to 50 nm, 10 to 50 nm, 10 to 30 nm, 7 to 30 nm, etc., but not limited thereto.
[0009] As a further improvement of the present invention, the porous silica particles have a BET specific surface area of 200 to 1000 m 2 Preferably, the porous silica particles have a BET specific surface area of 200 to 900 m 2 / g, more preferably, 200 to 700 m 2 / g, 200~600m 2 / g, 250~550m 2 / g, 300~500m 2 / g, etc., but not limited thereto, so that the povidone-iodine powder can be completely dispersed therein.
[0010] As a further improvement of the present invention, the mass ratio of the porous silica to povidone iodine is 10-30:0.5-1. Preferably, the mass ratio of the porous silica to povidone iodine is 10-30:0.8-1, and more preferably 10-20:0.8-1, 10-15:0.8-1.
[0011] The present application also provides a method for preparing the composite material for oral care agents, comprising the following steps: 1) preparing porous silica particles: dissolving 10 to 20 parts by weight of methyl orthosilicate in ethanol to obtain solution A; dissolving 3 to 5 parts by weight of ammonia water and 1 to 2 parts by weight of hexadecyltrimethylammonium chloride in deionized water to obtain solution B; adding solution B dropwise to solution A, heating to 50 to 80° C., stirring for reaction for 1 to 3 hours, filtering, washing, drying, and calcining at 400 to 500° C. for 1 hour to obtain the porous silica particles;
[0012] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 10-30:0.5-1, mix and put into a ball mill for ball milling, so that the povidone-iodine powder is completely dispersed in the pores inside the porous silica particles; whether the povidone-iodine powder is completely dispersed in the porous silica particles is determined by performing SEM test on the particles after ball milling to observe whether there are small powder particles attached to the surface of the spherical silica particles. If not, it means that the povidone-iodine powder is completely dispersed in the porous silica particles; if yes, continue ball milling;
[0013] 3) Take 200 mg of the ball-milled powder, disperse it in 10 mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes. Add 100-500 mg of β-cyclodextrin under stirring conditions, heat to 40-70° C. under a nitrogen atmosphere and react for 5-10 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and vacuum dry it at 50° C. for 24 hours to obtain the product.
[0014] As a further improvement of the present invention, in step 1), the volume ratio of solution A to solution B is 2 to 5:1.
[0015] As a further improvement of the present invention, the diameter of the porous silica particles obtained in step 1) is 50 to 1000 nm, and in the ball milling in step 2), the particle size of the porous silica particles is further reduced, so that the non-polar porous silica particles in the subsequent β-cyclodextrin coating can more smoothly enter the β-cyclodextrin hydrophobic cavity to achieve coating.
[0016] As a further improvement of the present invention, the step 1) is specifically as follows: 15 parts by weight of methyl orthosilicate is dissolved in 200 mL of ethanol to obtain solution A; 3 parts by weight of ammonia water and 1 part by weight of hexadecyltrimethylammonium chloride are dissolved in 100 mL of deionized water to obtain solution B; solution B is added dropwise to solution A, heated to 70° C., stirred for reaction for 2 h, filtered, washed, dried, and calcined at 400° C. for 1 h to obtain the product.
[0017] As a further improvement of the present invention, the step 3) is specifically as follows: take 200 mg of the ball-milled powder, disperse it in 10 mL of anhydrous ethanol, ultrasonically disperse it for 30 minutes, add 300 mg of β-cyclodextrin thereto under stirring conditions, heat to 50° C. under a nitrogen atmosphere and react for 10 hours, centrifuge the solution after the reaction, discard the supernatant, and vacuum dry it at 50° C. for 24 hours to obtain the product.
[0018] The present application also provides an application of the above composite material in an oral care agent, the composite material can be used as an abrasive and an antibacterial agent directly in toothpaste, the addition of abrasives and antibacterial additives is completed in one step when toothpaste is made, the operation of adding materials and mixing is reduced multiple times, and energy is saved; the composite material can also be used as an antibacterial disinfectant for dental floss surface coating and mouthwash antibacterial agent introduction, all of which have good stability and high sterilization and disinfection effects, and at the same time have good sustained-release effects, which can extend the sterilization time of oral care products. When the composite material is used in toothpaste, the β-cyclodextrin-coated silica abrasive has better dispersibility, which is convenient for dispersion during toothpaste mixing. When the toothpaste is used, the β-cyclodextrin will gradually destroy the integrity of the coating layer under the action of friction or digestive enzymes in saliva, so that the internal povidone-iodine effective ingredients are in contact with water, and the effective iodine is gradually released for sterilization and disinfection.
[0019] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0020] 1. The present invention provides a composite material that can be directly used in oral care products such as toothpaste, mouthwash, dental floss, etc. The material is safe and non-toxic, and fully utilizes the bactericidal effect of povidone iodine. No toxic raw materials are used in the preparation of the material, and the entire preparation process is green and environmentally friendly;
[0021] 2. The composite material structure of the present invention is novel in design. The special structure design can effectively disperse povidone iodine into the internal pores of silica. Multiple designs can effectively protect povidone iodine, so that povidone iodine is protected from the influence of light, oxygen, heat and water, thereby improving the stability of the antibacterial substance povidone iodine and maintaining its high effective iodine content. At the same time, the structure also increases the specific surface area of povidone iodine when it contacts water to a certain extent. When the oral care product is used, povidone iodine can quickly produce a large amount of active iodine after contacting water, thereby achieving a rapid sterilization effect.
[0022] 3. The raw material β-cyclodextrin can be degraded by digestive enzymes and microorganisms in the human body. As a common carbohydrate, it participates in the body's metabolism, has no accumulation effect, and is safe and non-toxic. At the same time, β-cyclodextrin also has certain antibacterial properties. The composite material has high stability, good overall antibacterial properties, and has a certain sustained-release effect, which increases the effective use time of the antibacterial agent. DETAILED DESCRIPTION
[0023] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0024] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0025] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. Povidone-iodine powder was purchased from BASF PVP-Iodine 30 / 60M10 (with an effective iodine content of 10.5%), and β-cyclodextrin was purchased from China Pharmaceutical (Group) Shanghai Chemical Reagent Company.
[0026] Example 1
[0027] A core-shell structure composite material is composed of a core composed of porous silicon dioxide particles and a coating shell composed of beta-cyclodextrin, wherein povidone-iodine is distributed in the pores of the porous silicon dioxide particles.
[0028] The composite material is prepared by the following method, comprising the following steps: 1) Preparation of porous silica particles: dissolving 10 parts by weight of methyl orthosilicate in 200 mL of ethanol to obtain solution A; dissolving 3 parts by weight of ammonia water and 1 part by weight of hexadecyltrimethylammonium chloride in 100 mL of deionized water to obtain solution B; adding solution B dropwise into solution A, heating to 50° C., stirring for reaction for 1 hour, filtering, washing, drying, and calcining at 400° C. for 1 hour to obtain porous silica particles with a diameter of 50 to 1000 nm;
[0029] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 10:1, mix them and put them into a ball mill to make the povidone-iodine powder completely dispersed in the pores inside the porous silica particles;
[0030] 3) Take 200 mg of the ball-milled powder, disperse it in 10 mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes. Add 100 mg of β-cyclodextrin under stirring conditions, heat to 40°C under a nitrogen atmosphere and react for 5 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and vacuum dry it at 50°C for 24 hours to obtain the product.
[0031] The obtained composite material was tested, wherein the porous silica particles had a diameter of 50 to 300 nm and a specific surface area of 200 to 1000 m 2 / g, the effective iodine content is 10.5%. The composite material is placed in a natural environment for 10 days, and the effective iodine content is 10.4% after testing.
[0032] Example 2
[0033] A core-shell structure composite material is composed of a core composed of porous silicon dioxide particles and a coating shell composed of beta-cyclodextrin, wherein povidone-iodine is distributed in the pores of the porous silicon dioxide particles.
[0034] The composite material is prepared by the following method, comprising the following steps: 1) Preparation of porous silica particles: dissolving 20 parts by weight of methyl orthosilicate in 500 mL of ethanol to obtain solution A; dissolving 5 parts by weight of ammonia water and 2 parts by weight of hexadecyltrimethylammonium chloride in 100 mL of deionized water to obtain solution B; adding solution B dropwise into solution A, heating to 80° C., stirring for reaction for 3 h, filtering, washing, drying, and calcining at 500° C. for 1 h to obtain porous silica particles with a diameter of 50 to 1000 nm;
[0035] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 30:0.5, mix them, and put them into a ball mill to make the povidone-iodine powder completely dispersed in the pores inside the porous silica particles;
[0036] 3) Take 200 mg of the ball-milled powder, disperse it in 10 mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes. Add 500 mg of β-cyclodextrin under stirring conditions, heat to 70°C under a nitrogen atmosphere and react for 10 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and vacuum dry it at 50°C for 24 hours to obtain the product.
[0037] The obtained composite material was tested, wherein the porous silica particles had a diameter of 50 to 250 nm and a specific surface area of 500 to 1000 m 2 / g, and the effective iodine content is 10.5%. The composite material is placed in a natural environment for 10 days, and the effective iodine content is 10.5% after testing.
[0038] Example 3
[0039] A core-shell structure composite material is composed of a core composed of porous silicon dioxide particles and a coating shell composed of beta-cyclodextrin, wherein povidone-iodine is distributed in the pores of the porous silicon dioxide particles.
[0040] The composite material is prepared by the following method, comprising the following steps: 1) Preparation of porous silica particles: 15 parts by weight of methyl orthosilicate is dissolved in 300 mL of ethanol to obtain solution A; 3 parts by weight of ammonia water and 2 parts by weight of hexadecyltrimethylammonium chloride are dissolved in 100 mL of deionized water to obtain solution B; solution B is added dropwise to solution A, heated to 70° C., stirred for reaction for 2 h, filtered, washed, dried, and calcined at 500° C. for 1 h to obtain porous silica particles with a diameter of 100 to 1000 nm;
[0041] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 20:1, mix them and put them into a ball mill to make the povidone-iodine powder completely dispersed in the pores inside the porous silica particles;
[0042] 3) Take 200 mg of the ball-milled powder, disperse it in 10 mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes. Add 300 mg of β-cyclodextrin under stirring conditions, heat to 50° C. under a nitrogen atmosphere and react for 8 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and vacuum dry it at 50° C. for 24 hours to obtain the product.
[0043] The obtained composite material was tested, wherein the porous silica particles had a diameter of 50 to 200 nm and a specific surface area of 300 to 800 m 2 / g, the effective iodine content is 10.5%. The composite material is placed in a natural environment for 10 days, and the effective iodine content is 10.4% after testing.
[0044] Comparative Example 1
[0045] A core-shell structure composite material is composed of a core composed of porous silicon dioxide particles and a coating shell composed of beta-cyclodextrin, wherein povidone-iodine is distributed in the pores of the porous silicon dioxide particles.
[0046] The composite material is prepared by the following method, comprising the following steps: 1) Preparation of porous silica particles: 15 parts by weight of methyl orthosilicate is dissolved in 300 mL of ethanol to obtain solution A; 3 parts by weight of ammonia water and 2 parts by weight of hexadecyltrimethylammonium chloride are dissolved in 100 mL of deionized water to obtain solution B; solution B is added dropwise to solution A, heated to 70° C., stirred for reaction for 2 h, filtered, washed, dried, and calcined at 500° C. for 1 h to obtain porous silica particles with a diameter of 100 to 1000 nm;
[0047] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 5:1, mix and put into a ball mill for ball milling. The povidone-iodine powder cannot be completely dispersed into the porous silica particles after long-term ball milling, and part of the povidone-iodine powder is distributed on the surface of the silica particles;
[0048] 3) Take 200 mg of the ball-milled powder, disperse it into 10 mL of deionized water, and ultrasonically disperse it for 30 minutes. Add 80 mg of β-cyclodextrin under stirring conditions, heat to 50°C under a nitrogen atmosphere and react for 8 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and then rinse with anhydrous ethanol and vacuum dry at 50°C for 24 hours.
[0049] The obtained composite material was tested, wherein the porous silica particles had a diameter of 50 to 200 nm and a specific surface area of 300 to 800 m 2 / g, the effective iodine content is 9.8%. The composite material is placed in a natural environment for 10 days, and the effective iodine content is 8.1% after testing.
[0050] Comparative Example 2
[0051] A core-shell structure composite material is composed of a core composed of porous silicon dioxide particles and a coating shell composed of beta-cyclodextrin, wherein povidone-iodine is distributed in the pores of the porous silicon dioxide particles.
[0052] The composite material is prepared by the following method, comprising the following steps: 1) Preparation of porous silica particles: 15 parts by weight of methyl orthosilicate is dissolved in 300 mL of ethanol to obtain solution A; 3 parts by weight of ammonia water and 2 parts by weight of hexadecyltrimethylammonium chloride are dissolved in 100 mL of deionized water to obtain solution B; solution B is added dropwise to solution A, heated to 70° C., stirred for reaction for 2 h, filtered, washed, dried, and calcined at 500° C. for 1 h to obtain porous silica particles with a diameter of 100 to 1000 nm;
[0053] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 20:1 and stir to mix;
[0054] 3) Take 200 mg of the mixed powder, disperse it in 10 mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes. Add 300 mg of β-cyclodextrin under stirring conditions, heat to 50° C. under a nitrogen atmosphere and react for 8 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and vacuum dry it at 50° C. for 24 hours to obtain the product.
[0055] The obtained composite material was tested, wherein the porous silica particles had a diameter of 50 to 1000 nm and a specific surface area of 300 to 800 m 2 / g, the effective iodine content is 10.1%. The composite material is placed in a natural environment for 10 days, and the effective iodine content is 8.5% after testing.
[0056] Comparative Example 3
[0057] A povidone-iodine and beta-cyclodextrin composite material consists of povidone-iodine and beta-cyclodextrin coated on the surface of the povidone-iodine.
[0058] The composite material is prepared by the following method, comprising the following steps: weighing 300 mg of β-cyclodextrin, dispersing it into 10 mL of anhydrous ethanol, adding 200 mg of povidone iodine powder thereto under stirring conditions, ultrasonically dispersing for 30 minutes, heating to 50° C. under a nitrogen atmosphere and reacting for 8 hours, and vacuum drying at 50° C. for 24 hours to obtain the composite material.
[0059] The obtained composite material was tested, wherein the effective iodine content was 3.2%. The composite material was placed in a natural environment for 10 days, and the effective iodine content was 2.8%.
[0060] Comparative Example 4
[0061] A porous silicon dioxide and povidone-iodine composite material, wherein povidone-iodine is distributed in the pores of the porous silicon dioxide particles.
[0062] The composite material is prepared by the following method, comprising the following steps: 1) Preparation of porous silica particles: 15 parts by weight of methyl orthosilicate is dissolved in 300 mL of ethanol to obtain solution A; 3 parts by weight of ammonia water and 2 parts by weight of hexadecyltrimethylammonium chloride are dissolved in 100 mL of deionized water to obtain solution B; solution B is added dropwise to solution A, heated to 70° C., stirred for reaction for 2 h, filtered, washed, dried, and calcined at 500° C. for 1 h to obtain porous silica particles with a diameter of 100 to 1000 nm;
[0063] 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 20:1, mix them, and put them into a ball mill for ball milling, so that the povidone-iodine powder is completely dispersed in the pores inside the porous silica particles.
[0064] The obtained composite material was tested, wherein the porous silica particles had a diameter of 50 to 200 nm and a specific surface area of 300 to 800 m 2 / g, the effective iodine content is 10.4%. The composite material is placed in a natural environment for 10 days, and the effective iodine content is 8.9% after testing.
[0065] Comparative Example 5
[0066] PVP-Iodine 30 / 60M10 purchased from BASF was tested and found to have an effective iodine content of 10.5%. After being placed in a natural environment for 10 days, the effective iodine content was found to be 7.2%.
[0067] From the test results in the above embodiments and comparative examples, it can be seen that the composite material obtained by the embodiment of the present application has a high effective iodine retention rate. After being placed in a natural environment for 10 days, the effective iodine content remains basically unchanged. It can be seen that the specific product structure obtained by the specific method of the present application can achieve effective protection of the antibacterial agent povidone iodine, so that povidone iodine can be protected from the influence of light, oxygen, heat, water, etc. in the environment, improves the stability of povidone iodine, and maintains its high effective iodine content. Povidone iodine powder without any treatment is continuously released and consumed from povidone iodine due to the influence of moisture in the air, resulting in a decrease in its effective iodine; povidone iodine that has not been coated with β-cyclodextrin or composited with porous silica particles has a phenomenon of a decrease in effective iodine content after being placed for a period of time, which also shows from the side that although the solubility of povidone iodine is improved, the stability of effective iodine is still not high.
[0068] The above is a detailed introduction to an oral care agent. The above content is a further detailed description of the present invention in combination with specific preferred embodiments. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the patent protection scope of the present invention determined by the submitted claims.
Claims
1. A composite material for an oral care agent, characterized in that: The composite material is a core-shell structure, the core is porous silicon dioxide particles, povidone iodine is distributed in the pores of the porous silicon dioxide particles, and the shell is beta-cyclodextrin.
2. The composite material for oral care agent according to claim 1, characterized in that: The porous silica particles have a diameter of 50 to 300 nm.
3. The composite material for oral care agent according to claim 2, characterized in that: The specific surface area of the porous silica particles is 200 to 1000 m 2 / g.
4. The composite material for oral care agent according to claim 1, characterized in that: The mass ratio of the porous silicon dioxide to povidone iodine is 10-30:0.5-1.
5. A method for preparing the composite material according to claim 1, characterized in that: The method comprises the following steps: 1) preparing porous silica particles: dissolving 10 to 20 parts by weight of methyl orthosilicate in ethanol to obtain solution A; dissolving 3 to 5 parts by weight of ammonia water and 1 to 2 parts by weight of hexadecyltrimethylammonium chloride in deionized water to obtain solution B; adding solution B dropwise into solution A, heating to 50 to 80° C., stirring for reaction for 1 to 3 hours, filtering, washing, drying, and calcining at 400 to 500° C. for 1 hour to obtain the porous silica particles; 2) Weigh porous silica particles and povidone-iodine powder in a mass ratio of 10-30:0.5-1, mix them and put them into a ball mill to make the povidone-iodine powder completely dispersed in the pores inside the porous silica particles; 3) Take 200 mg of the ball-milled powder, disperse it in 10 mL of anhydrous ethanol, and ultrasonically disperse it for 30 minutes. Add 100-500 mg of β-cyclodextrin under stirring conditions, heat to 40-70° C. under a nitrogen atmosphere and react for 5-10 hours. After the reaction is completed, centrifuge the solution, discard the supernatant, and vacuum dry it at 50° C. for 24 hours to obtain the product.
6. The preparation method according to claim 5, characterized in that: In the step 1), the volume ratio of solution A to solution B is 2-5:
1.
7. The preparation method according to claim 5, characterized in that: The diameter of the porous silica particles obtained in step 1) is 50 to 1000 nm.
8. The preparation method according to claim 5, characterized in that: The step 1) is specifically as follows: dissolving 15 parts by weight of methyl orthosilicate in 200 mL of ethanol to obtain solution A; dissolving 3 parts by weight of ammonia water and 1 part by weight of hexadecyltrimethylammonium chloride in 100 mL of deionized water to obtain solution B; adding solution B dropwise into solution A, heating to 70° C., stirring for reaction for 2 h, filtering, washing, drying, and calcining at 400° C. for 1 h to obtain the product.
9. The preparation method according to claim 5, characterized in that: The step 3) is specifically as follows: 200 mg of the ball-milled powder is dispersed in 10 mL of anhydrous ethanol, and ultrasonically dispersed for 30 min, 300 mg of β-cyclodextrin is added thereto under stirring conditions, and the mixture is heated to 50° C. and reacted for 10 h under a nitrogen atmosphere. After the reaction is completed, the solution is centrifuged, the supernatant is discarded, and the mixture is vacuum dried at 50° C. for 24 h to obtain the product.
10. Use of the composite material according to any one of claims 1 to 4 in an oral care agent, characterized in that: The composite material is directly used in toothpaste as an abrasive and an antibacterial agent.
Citation Information
Patent Citations
Nano-silver mouth wash for preventing and treating oral diseases and preparation method thereof
CN103385804A
Stable compositions of uncomplexed iodine and methods of use
CN106163577A
Oral sterilization and disinfection mouthwash and preparation method and use method thereof
CN110037940A
Inhalation powder mist preparation for preventing and treating respiratory tract infectious diseases
CN113244262A
Povidone iodine toothpaste and preparing method
CN1245954C